Effects of pyridinic N of carboxylic acid on the polymerization of polyaniline and its supercapacitor performances - Yazar, Sibel; Arvas, Melih Besir; Yilmaz, Sila Melahat; Sahin, Yucel (ELSEVIER, 2022)
Phthalic acid and 2,3-pyrazinedicarboxylic acid doped PANI were synthesized on carbon felt electrode by a simple hydrothermal method. A systematic study was done to show the effect of carboxylic acid groups and pyrazine moiety on the energy storage properties of polyaniline and the obtained electrodes were characterized using X-ray photoelectron spectroscopy, X-ray diffraction, Fourier Transform Infrared spectroscopy, Thermog-ravimetric analysis, Brunauer-Emmett-Teller surface area analysis and Scanning Electron Microscopy. Better specific capacitance of polyaniline (PANI) was observed in the presence of 2,3-pyrazinedicarboxylic (Pzdc) acid. The strengthening of electron delocalization of the PANI structure with pyridine N, the increase of 7C-7C in-teractions and the formation of hydrogen bonds with the effect of carboxyl groups in the 2,3 pyrazine dicar-boxylic acid contributed to the improvement of the energy storage properties of PANI. (Strengthening electron delocalization of the PANI structure with pyridine N, increased 7C-7C interactions, and the formation of hydrogen bonds under the influence of carboxyl groups in the 2,3 pyrazine dicarboxylic acid contributed to the improvement of the energy storage properties of PANI.)Moreover, the study focused on showing the effect of the 2,3-pyrazinedi carboxylic acid ratio on its charge storage properties. Electrochemical measurements were carried out in 3.0 M KCl aqueous electrolyte solution. The results show that the high specific capacitance of 882.0 F g-1 is observed for Pzdc(0.02)/PANI electrode at the current density of 7 A g-1. Further, the supercapacitor electrode performed a good cycling test (96.7 %) after 2000 cycles with a high operating potential of 1.5 V. The fabricated symmetrical supercapacitor device has high cyclic stability and good electrochemical performance (energy density of 27.2 Wh kg-1 and 81.7 % at 2500 cycles).
Keywords: 3-Pyrazinedicarboxylic acid; Polyaniline; Carbon felt; Supercapacitor; Hydrothermal method; CARBON-CLOTH; ELECTROCHEMICAL CAPACITORS; THERMAL-DEGRADATION; ELECTRODE MATERIALS; VOLTAGE WINDOW; PHTHALIC-ACID; HIGH-ENERGY; FABRICATION; COMPOSITE; NITROGEN; Energy & Fuels